2021
DOI: 10.3390/agronomy11030466
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Irrigation and Nitrogen Fertilization on Seed Yield, Yield Components, and Water Use Efficiency of Cleistogenes songorica

Abstract: Irrigation and nitrogen (N) are two crucial factors affecting perennial grass seed production. To investigate the effects of irrigation and N rate on seed yield (SY), yield components, and water use efficiency (WUE) of Cleistogenes songorica (Roshevitz) Ohwi, an ecologically significant perennial grass, a four-year (2016–2019) field trial was conducted in an arid region of northwestern China. Two irrigation regimes (I1 treatment: irrigation at tillering stage; I2 treatment: irrigation at tillering, spikelet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Similarly, most crop irrigation is also a process of post-drought rewatering. The irrigation is usually accompanied by nitrogen fertilizer application to increase the crop water use efficiency (Tao et al, 2021 ; Zain et al, 2021 ). The coexistence of soil heterotrophic AOB with crops can increase the timely irrigation water use, which plays a potential role in replacing nitrogen fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, most crop irrigation is also a process of post-drought rewatering. The irrigation is usually accompanied by nitrogen fertilizer application to increase the crop water use efficiency (Tao et al, 2021 ; Zain et al, 2021 ). The coexistence of soil heterotrophic AOB with crops can increase the timely irrigation water use, which plays a potential role in replacing nitrogen fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the WS treatment applied in C. songorica enhanced carbon remobilization in the sources and increased the seed yield per spike by increasing the seed number per spike (CL spikes and CH spikes), especially in CL_B spikes and CL_M spikes, where it increased 2.25 and 1.6 times, respectively. The seed number was one of the components of seed yield, and seed yield per plant was improved when the seed number per spike was increased (Li et al, 2014; Tao et al, 2021). Therefore, a well-controlled balance between source and sink at the initial flowering stage was pivotal for C. songorica production under the WS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the seed supply is insufficient due to the low seed yield of C. songorica , which limits its large-scale application in many fields, such as ecological restoration and grassland development (Li et al, 2014; Tao et al, 2018). Previous studies have shown that irrigation at the early flowering stage is an important aspect of successful seed production (Tao et al, 2021). However, the potential role of gene regulation in the WS-induced improvement of carbon reserve remobilization from source (stems, leaves and sheaths) sites, and the interaction between sources, CL spikes and CH spikes at the transcriptional level is not clear in C. songorica .…”
Section: Introductionmentioning
confidence: 99%